Analysis of Parenting Patterns and Nutritional Imbalance as Risk Factors for Stunting in Toddlers - Hariati, Niken Widyastuti; Aprianti, Aprianti (Sarana Ilmu Indonesia (salnesia), 2025)
Stunting is a chronic nutritional problem that has serious impacts on children's physical growth and cognitive development. In 2023, South Kalimantan Province recorded a stunting prevalence of 24,7%, higher than the national average of 21,5%. This study aimed to examine the feeding practices and nutritional intake balance among stunted children under five in the Sungai Ulin Community Health Center (Puskesmas) service area. The study employed a mixed-methods approach, consisting of a quantitative component using a cross-sectional design, and a qualitative component through in-depth interviews. The quantitative data sample included 66 stunted children aged ?1 year, while the qualitative data sample consisted of 15 mothers or caregivers of stunted children. Data collection and analysis were conducted from March to July 2024. The study findings indicated that 54,5% of the stunted children were under three years old, and 60,6% were male. Additionally, 57,6% of the children had a short stature nutritional status. Energy (51,5%), carbohydrate (63,6%), and iron (57,6%) intake deficits were identified as significant risk factors. The qualitative findings revealed that parental time availability nutritional knowledge, and improper complementary feeding practices contributed to the occurrence of stunting. Interventions promoting balanced diets and educating parents about appropriate feeding practices are essential steps in preventing stunting.